2018
DOI: 10.1371/journal.pntd.0006722
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne zoonoses in the Order Rickettsiales and Legionellales in Iran: A systematic review

Abstract: BackgroundTick-borne zoonoses in the Order Rickettsiales and Legionellales cause infections that often manifest as undifferentiated fevers that are not easy to distinguish from other causes of acute febrile illnesses clinically. This is partly attributed to difficulty in laboratory confirmation since convalescent sera, specific diagnostic reagents, and the required expertise may not be readily available. As a result, a number of tick-borne zoonoses are underappreciated resulting in unnecessary morbidity, morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 204 publications
(236 reference statements)
0
15
0
Order By: Relevance
“…They are transmitted to humans by vector arthropods such as ticks, fleas and lice [42 -47]. In the Middle East, a number of known species of Rickettsia genus have been reported, but some studies are suspicious [48]. Al-Deeb et al reported the first case of spotted fever group of Rickettsia sp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They are transmitted to humans by vector arthropods such as ticks, fleas and lice [42 -47]. In the Middle East, a number of known species of Rickettsia genus have been reported, but some studies are suspicious [48]. Al-Deeb et al reported the first case of spotted fever group of Rickettsia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Mediterranean Spotted Fever (MSF) is caused by Rickettsia conorii subsp. Israelensis is the main cause of fever and chills from spotted fever group rickettsiosis in collected ticks from mice, deers, goats, red foxes and wild boars [48,51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Israelensis as a main cause of fever and chills from spotted fever group rickettsiosis in collected ticks from mice, deers, goats, red foxes and wild boars(48,51).According to conducted studies in the Middle East, the presence of different types of ticks, which can Despite the evidence of presence of Rickettsial SFG pathogens in the Middle East, there is no study on this disease in Iran.Therefore, it is necessary to study the SFG Rickettsiae to better understand the epidemiology of this disease in Iran(48). There is only a paper on the spotted-fever group rickettsioses and it investigates 40 samples of human serum collected from 4 countries including Iran for the presence of spotted fever group rickettsia antibodies among other pathogens by Kovacova et al From 40 human laboratory samples, 45% were positive in terms of SFG rickettsia by the ELISA test, and 27.5% were positive using the IFA test(48,54).…”
mentioning
confidence: 99%